Literasi informasi : peningkatan kompetensi informasi dalam proses pembelajaran - Pattah, Sitti Husaebah (Program Studi Ilmu Perpustakaan UIN Alauddin, 2014)
The development of knowledge and life became ease with the presence of information communication and technology, particularly internet. Information literacy is needed to access any form of information through the internet. Academicians are expected to be information literate. They should use and evaluate information resources, especially from the internet in any kind of learning process. The ability to be literate in library services is necessary important in order to optimize library resources and services. Besides, information literacy tells end-users to recognize information sources and can be ease to find the needed information from different and varieties sources. Many models of information literacy are implemented in many libraries in which the objective is to enhance literacy skills for library users.